ANALISIS YURIDIS PENGANGKATAN DAN PEMBERHENTIAN KEPALA POLISI REPUBLIK INDONESIA MENURUT UNDANG-UNDANG NOMOR 2 TAHUN 2002 TENTANG KEPOLISIAN REPUBLIK INDONESIA DAN SIYASAH DUSTURIYAH - Mezi Nikmat; Ade Kosasih; Masril Masril (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: The approval of the DPR in the appointment and dismissal of the Chief of Police of the Republic of Indonesia by the President reaps the Pros and Cons of various academics and practitioners of Constitutional Law, is one of the reasons for the writing of this thesis. The type of research in the writing of this thesis is juridical normative with the legal interpretation method used by the author is the grammatical, functional and systematic interpretation of the mechanism for the appointment and dismissal of the Police Chief of the Republic of Indonesia so that it can be seen how the considerations of the forming of Law Number 2 of 2002 concerning the Indonesian National Police in The appointment of the Police Chief of the Republic of Indonesia must obtain the approval of the DPR and to find out how Siyasah views the appointment and dismissal of the National Police Chief. Based on the research results, the mechanism for the appointment and dismissal of the Chief of Police is the authority of the President after obtaining approval from the DPR. Whereas in the Siyasah Fiqh the process of appointing and dismissing the Police Chief (Shahib asy-Syurthah) is directly appointed by the caliph / head of the State without any interference from other institutions.Keywords: Police Chief Appointment; DPR approval; Fiqh Siyasah